Substansi Perubahan Sistem Pemilu Dan Implikasinya Berdasarkan Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum Serta RKPD Tahun 2018 Sesuai Permendagri Nomor 32 Tahun 2017 (Pendampingan Bimbingan Teknis Nasional Anggota DPRD Kota Sungai Penuh) - A. H. Rahadian; Resista Vikaliana; Munir Saputra (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2019)
In order to increase the capacity of the Sungai Penuh City Leaders and Members of the DPRD and based on legislation. The Institute for Research and Community Service of the STIAMI Institute of Social Sciences and Management (LPPM - Institut STIAM) Jakarta, has organized National Technical Guidance, in the form of presentations and discussions with the theme: "Substance of Election System Change and Its Implications Based on Law Number 7 of 2017 concerning Election General and RKPD Year 2018 According to Permendagri Number 32 Year 2017 ". Methods and Learning Techniques, namely lectures giving material by the resource person and discussion and question and answer, namely participants are given the opportunity to ask questions about problems that occur in the region, so that solutions can be overcome. The conclusion of the implementation of Technical Guidance, based on evaluation, can be stated (1). The speakers presented as a whole have satisfied Bimtek participants, (2). Evaluations of relevance, methods and media, facilities and consumption were assessed by the majority of participants as satisfying (3). The learning process is very interesting so there is a 2-way communication between the speaker and the participants where the discussion appears. It is suggested that in the context of the performance of DPRD members, of course this kind of activity must continue to be carried out by observing the latest topics so that implementatively participants can obtain new knowledge, then it is important to always pay attention to quality and service improvement so that implementation can run better.